Review and outlook of solar energetic particle measurements on multispacecraft missions - Reames, Donald V. (Frontiers in Astronomy and Space Sciences, 2023)
The earliest evidence on spatial distributions of solar energetic particles (SEPs) compared events from many different source longitudes on the Sun, but the early Pioneers provided the first evidence of the large areas of equal SEP intensities across the magnetically-confined "reservoirs" late in the events. Moredetailed measurements of the importance of self-generated waves and trapping structures around the shock waves that accelerate SEPs were obtained from the Helios mission plus IMP 8, especially during the year when the two Voyager spacecraft also happened by. The extent of the dozen widest SEP events in a solar cycle, that effectively wrap around the Sun, was revealed by the widely separated STEREO spacecraft with three-point intensities fit to Gaussians. Element abundances of the broadest SEP events favor average coronal element abundances with little evidence of heavy-element-enhanced "impulsive suprathermal" ions that often dominate the seed population of the shocks, even in extremely energetic local events. However, it is hard to define a distribution with two or three points. Advancing the physics of SEPs may require a return to the closer spacing of the Helios era with coverage mapped by a half-dozen spacecraft to help disentangle the distribution of the SEPs from the underlying structure of the magnetic field and the accelerating shock.